Ghostgirl : homecoming - Hurley, Tonya (New York : Little, Brown, 2010)
When Petula becomes deathly ill, her sister Scarlet seeks help from former classmate Charlotte, for whom the afterlife has become burdensome, leaving her just as insecure and isolated as she was while she was alive.
School Library Journal, August 2009
Young Adult
Young Adult
School Library Journal
910
Keywords: Future life -- Juvenile fiction; Sisters -- Juvenile fiction; Coma -- Juvenile fiction; Death -- Juvenile fiction; Friendship -- Juvenile fiction; Future life -- Fiction; Sisters -- Fiction; Coma -- Fiction; Death -- Fiction; Friendship -- Fiction; Future life -- Fiction; Sisters -- Fiction; Coma -- Fiction; Death -- Fiction; Friendship -- Fiction